Comparison of the Characteristics and Risk Factors of Carotid Atherosclerosis in High Stroke Risk Populations Between Urban and Rural Areas in North China - Zhang, Jin; Sang, Hui; Zhang, Xin; Fang, Yalan; Niu, Xiaoyuan; Liu, Tingting; Liu, Weidong; Li, Jian (Frontiers in Neurology, 2020)
Objective: To study the characteristics and risk factors of carotid atherosclerosis in populations at high risk of stroke in urban and rural areas of North China. Methods: A cross-sectional study was conducted to investigate high stroke risk populations in representative urban and rural areas sampled from 12 regions of China. A pre-designed questionnaire, ultrasound and laboratory examinations were performed to evaluate risk factors. Results: A total of 30,175 patients were included in the study. The overall prevalence of carotid atherosclerosis was 54.53%, among which intimal thickening and plaque were 39.22% and 41.25%, respectively. The prevalence of carotid atherosclerosis in the urban group was higher than the rural group. Multivariate logistic regression analysis revealed that male, age, smoking, hypertension, dyslipidemia, stroke, atrial fibrillation, systolic blood pressure, and levels of fasting blood glucose, total cholesterol, and low-density lipoprotein cholesterol were the common independent risk factors for carotid atherosclerosis in both groups. Higher education, high salt consumption, passive smoking, family history of stroke, and transient ischemic attack were unique independent risk factors, and high-density lipoprotein cholesterol was a protective factor for carotid atherosclerosis in the urban population. Conclusion: This study suggests that risk factors for carotid atherosclerosis differ between urban and rural populations in North China.